Making Government an Effective Partner : Civil Service Reform in Sub-Saharan Africa - Dia, Mamadou (World Bank, Washington, DC, 2012)
The paper previewed in this article focuses on the implementation of a long-term capacity building approach to civil service reform. It starts with a review of past World Bank support to civil service reform and confirms that the cost containment approach achieved neither fiscal stabilization nor efficiency objectives despite heavy political and social costs. The rather disappointing results are traced to the patrimonial character of the state whose features in the civil service context are: recruitment based on subjective and ascriptive criteria; public employment managed as a welfare system; pay levels that are unrelated to productivity; loyalty of officials to the person of the ruler rather than to the state; and formalism of administrative rules and procedures rather than the substance. The paper argues that the direction of improvement lies in improved governance; a broader approach to civil service reform. Improving governance would begin with an assessment of the institutional environment which determines the patrimonial profile of the country: high when all of these factors are absent, low when they are present. This would be followed by the adoption of a strategy for reform that could be a comprehensive approach, an enclave approach or a hybrid approach, depending on whether the country's patrimonial profile is high, low or average, respectively.